2022
DOI: 10.55563/clinexprheumatol/mccyj0
|View full text |Cite
|
Sign up to set email alerts
|

Increased interleukin-11 associated with disease activity and development of interstitial lung disease in patients with rheumatoid arthritis

Abstract: ObjectiveTo investigate the association of serum with disease activity and occurrence of interstitial lung disease (ILD) in patients with rheumatoid arthritis (RA). MethodsOne hundred and six RA patients were included, including 31 with ILD. All patients were divided into two groups according to the 28-joint Disease Activity Score (DAS28), active-disease group (DAS28>3.2) and target-achieved group (DAS28≤3.2). Serum IL-11 was detected by ELISA. Serum autoantibodies [anticitrullinated protein antibody (ACPA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
(20 reference statements)
0
8
0
Order By: Relevance
“… 6 More recently, it has been studied in different systemic diseases and has been broadly described to be anti-inflammatory; however, very little is known about its role in the eye. 32 , 33 Beyond a single study by Nagineni et al 13 reporting expression of IL-11 in primary cultures of human retinal pigment epithelial cells and corneal fibroblast cells in vitro, no study has investigated the role of IL-11 in corneal diseases and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“… 6 More recently, it has been studied in different systemic diseases and has been broadly described to be anti-inflammatory; however, very little is known about its role in the eye. 32 , 33 Beyond a single study by Nagineni et al 13 reporting expression of IL-11 in primary cultures of human retinal pigment epithelial cells and corneal fibroblast cells in vitro, no study has investigated the role of IL-11 in corneal diseases and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, such observations warrant further investigation since, as an example, IL-4 is a strict autocrine cytokine and serum levels may not differ even between subjects with IL-4-dependent diseases and healthy controls ( 119 ). Both arthritis and ILD severity correlate with the presence and serum concentrations of IL-11 and IL-33, independent of the RF and ACPA status, with the former being also associated with RA disease activity ( 93 , 94 ). Within the IL23-IL17 axis, Zhang and colleagues reported that lung fibroblasts from patients with RA-ILD express significantly higher levels of the IL-17A receptor (IL-17RA) compared to patients without ILD or IPF ( 120 ) while IL-23 contributes to the epithelial-mesenchymal transition in the lung of RA-ILD ( 121 ).…”
Section: Traditional and Novel Biomarkers In Ra-ildmentioning
confidence: 99%
“…The scientific community working on lung fibrosis was quick to embrace the idea that IL11 is an important pro-fibrotic factor and a number of publications have validated and extended findings: 2020, IL11/ERK signalling is important for senescence of lung cells [ 68 ] and fibroblast-specific expression of IL11 causes lung fibro-inflammation [ 140 ]; 2021, IL11 expression is associated with lung fibrosis in patients with rheumatoid arthritis [ 153 ], replication of IL11 up-regulation and its effects in bleomycin injury and HPS [ 154 ]; 2022, nanoparticle delivery of siRNA against Il11 reduces lung fibrosis in the bleomycin mouse model [ 155 ], IL11 contributes to pulmonary artery remodelling and fibrosis in pulmonary hypertension [ 90 ], therapeutic targeting of IL11 reduces lung fibro-inflammation due to silica particle inhalation [ 156 ]; 2023, anti-IL11 reduces emphysematous disease in a mouse model of Marfan syndrome [ 157 ], IL11 disrupts alveolar epithelial cell repair functions by causing EMT [ 103 , 104 ], IL11 is elevated in interstitial lung disease in systemic sclerosis [ 158 , 159 ] and IL11 contributes to lung fibrosis in patients with SARS-COV-2 [ 160 , 161 ].…”
Section: Lung Diseasementioning
confidence: 99%
“…In synovial tissues from patients with RA, IL11 and IL11RA are up-regulated in synovial fibroblasts and IL11 secreted from fibroblasts stimulates ECs to promote neo-vascularisation [ 113 ]. Of note, IL11 levels, while increased in patients with RA in general, are specifically elevated in patients with active disease or RA-ILD [ 153 ].…”
Section: Autoimmune Diseasesmentioning
confidence: 99%